Indonesian Diplomacy in Fulfilling the Right to Learn for Children of Indonesian Migrant Workers in Johor (2023-2025) - Suwarti Sari; Bimbi Rianda (Universitas Jenderal Ahmad Yani, 2026)
This study critically examines the Indonesian government’s diplomatic efforts to protect and fulfill the educational rights of children of Indonesian migrant workers (PMI) in Johor, Malaysia. It specifically interrogates the challenges faced by children of informal sector workers, frequently undocumented, due to Malaysia’s regulations prohibiting informal migrant workers from marrying and starting families, which produce systemic barriers. Indonesia’s response leverages educational diplomacy and soft power, yet these measures are tested by regulatory constraints. The study identifies Community Learning Centers (CLCs) as a calculated transnational intervention, though they remain constrained by host-country sovereignty.